The solidarity motive - Christoph Engel (Max Planck Institute for Research on Collective Goods, 2016)
For decades, experimental economics has been very interested in behavior that could be characterized as practicing solidarity (although the term is rarely used). Solidarity is a key concept in Catholic Social Teaching. This paper builds a bridge between these two endeavors that, thus far, had little contact with each other. Catholic Social Teaching is essentially normative. People are informed what they should do if they are good Christians. Experimental Economics is descriptive. Experimenters want to learn how much solidarity experimental participants exhibit when this is costly. But from a Catholic perspective it is interesting how strongly their norms are reflected in actual behavior. The many distinctions uncovered by behavioral economics may also help refine Catholic thinking. And behavioral economics is confronted with new questions, in particular regarding deontological motives.
Keywords: A12; A13; C91; D03; D63; D64; Z12; 330; solidarity; dictator game; stealing game; public good game; social preferences; Deonto-logical Motives